(3JbGSje GdYdds - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s
(3ChdgG (B:s
(3bGd eMeO Hf RcQjG GdQGRi (B: (3LQi HMVQI QLd aGVd PcQ JbGSje GdYdd hYdGeGJgG , aQCjJ Cf CDda cJGHkG ai gPG GdeYfi faYg hjcKQ ZfGDg dLejY GdfGXQjf ajg hGdeSJYedjf dg s
(3BNQgG (B:s
(3hMJi jPgH GdYWT , aEf COgGf GdMeGe hGdJOHjQ GdeSef ddHOf hGdCOhjI GdJi JbdY Gdcda jPgHgG Ef TGA Gddg JYGdi s
(3Vef eLehY , JQJjHgG (B: (3ef U (B186 - (3U(B236s
(3GfXQg eY HSJGf GdCWHGA dGHf GdeWQGf Qbe(B" 3490_ 351 "s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA WH (B- (3bSe GdcJGH GdKGfi (B- (3U (B63 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdWHs